Disability and the Hebrew Bible: A Survey and Appraisal. (October 2019) - Melcher, Sarah
This article provides an overview and analysis of some significant studies on disability in the Hebrew Bible. The discussion of scholarly works proceeds chronologically, from earlier to later publications. Many different methods are applied in these studies, representing various types of biblical criticisms as well as approaches gleaned from disability studies. All have merit, but the most helpful of these combine a working knowledge of disability studies with historical and literary criticisms as practiced by skilled biblical scholars. Some of these authors contend that cultural criticism is the best approach borrowed from disability studies. While this article surveys these analyses holistically, in the case of anthologies, two or more exemplary essays are lifted out for consideration. These serve as examples of the types of investigations that are being done in the field of disability studies and the Bible.